2000
DOI: 10.1093/ps/79.4.539
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary vitamin E on the quality of table eggs enriched with n-3 long-chain fatty acids

Abstract: Because of the proposed cardioprotective benefits of n-3 fatty acids and vitamin E, a trial was carried out to investigate the possibility of enriching eggs with n-3 fatty acid and vitamin E added to the hen's diet. One hundred ninety-two Hy-Line Brown hens, 39-wk-old, were divided into eight groups: four groups received the basal diet supplemented with 3% lard and four doses of dl-alpha-tocopheryl acetate (0, 50, 100, and 200 ppm), whereas the diets of the other groups were supplemented with 3% of fish oil an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
82
2
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 17 publications
26
82
2
6
Order By: Relevance
“…Generally, the concentrations of n-3 PUFA increased, whereas n-6 PUFA tended to decrease in yolk lipids, and the fatty acid composition of the yolks reflected the dietary fish oil levels. The changes in yolk n-3 PUFA shown here due to feeding graded levels of fish oil (Table 2) are in agreement with previous reports (Meluzzi et al, 2000;Gonzalez-Esquerra and Leeson, 2000). Meluzzi et al (2000) indicated that the treatment with 3% fish oil caused a dramatic increase (P < 0.01) in all n-3 fatty acids of the yolk, particularly EPA and DHA, and caused an appreciable decrease in arachidonic acid (ARA, 20 : 4(n-6)).…”
Section: --supporting
confidence: 92%
See 2 more Smart Citations
“…Generally, the concentrations of n-3 PUFA increased, whereas n-6 PUFA tended to decrease in yolk lipids, and the fatty acid composition of the yolks reflected the dietary fish oil levels. The changes in yolk n-3 PUFA shown here due to feeding graded levels of fish oil (Table 2) are in agreement with previous reports (Meluzzi et al, 2000;Gonzalez-Esquerra and Leeson, 2000). Meluzzi et al (2000) indicated that the treatment with 3% fish oil caused a dramatic increase (P < 0.01) in all n-3 fatty acids of the yolk, particularly EPA and DHA, and caused an appreciable decrease in arachidonic acid (ARA, 20 : 4(n-6)).…”
Section: --supporting
confidence: 92%
“…The changes in yolk n-3 PUFA shown here due to feeding graded levels of fish oil (Table 2) are in agreement with previous reports (Meluzzi et al, 2000;Gonzalez-Esquerra and Leeson, 2000). Meluzzi et al (2000) indicated that the treatment with 3% fish oil caused a dramatic increase (P < 0.01) in all n-3 fatty acids of the yolk, particularly EPA and DHA, and caused an appreciable decrease in arachidonic acid (ARA, 20 : 4(n-6)). Similar results were reported by Huang et al (1990) who found that the n-3 PUFA content of the yolk is positively related to the addition of fish oil at the rate of 2%, 3% or 4% to the diet.…”
Section: --supporting
confidence: 92%
See 1 more Smart Citation
“…Yu (1994) have reported that VE is an excellent biological chain-breaking antioxidant that protects cells and tissues from lipoperoxidative damage. Various studies also reported that the amount of VE in yolk was associated with the amount of VE in the diet and confirmed a linearly increased relationship between dietary a-tocopheryl acetate supplementation level and a-tocopheryl egg yolk concentration (Meluzzi et al 2000;Grobas et al 2002). Similar with the current study, the inclusion of VE led to a greater VE concentration in egg yolk compared with CON group, which confirmed that the egg yolk VE concentration is related to the VE amount in the diets.…”
Section: Effect Of Ve Supplementation In Laying Hensupporting
confidence: 89%
“…In contrast, it was noted that less food was consumed by hamsters fed fish oil-containing diets supplemented with vitamin E than unsupplemented diets, while BWG was not affected by vitamin E supplementation (Poirier et al, 2002). In a study conducted with layer hens, it was found that vitamin E supplementation at different levels to diets enriched with PUFAs did not affect performance (Meluzzi et al, 2000;Sijben et al, 2002) and in contrast to these studies, Scheideler & Froning (1996) noted that vitamin E supplementation (50 IU/kg) to a diet enriched with n-3 PUFAs significantly improved egg production in layer hens. While some reports (Coetzee Guo et al, 2001;Özkan et al, 2007) describe a lack of response in performance to supplementation with vitamin E under normal conditions, others have shown improvements in performance.…”
Section: Resultsmentioning
confidence: 97%